Cutaneous phaeohyphomycosis in a greater bulldog bat (Noctilio leporinus) in northeastern Brazil. (February 2023) - Souto, E.P.F.; Oliveira, A.M.; Hoffmann, A.R.; Mota, R.A.; Galiza, G.J.N.; Dantas, A.F.M.
Abstract: An adult male greater bulldog bat ( Noctilio leporinus ) was found dead in a suburban area in the municipality of Patos, Paraiba, northeastern Brazil. At post-mortem examination, the bat was emaciated and had multifocal to coalescent grey, crusted, dry, scaly cutaneous lesions, irregularly distributed over the dorsal thoracoabdominal region, muzzle, labial commissures, ears and dorsoventral surfaces of the patagia. Histopathology revealed numerous longitudinal and transverse sections of fungal organisms, with weakly basophilic walls, associated with multifocal areas of ulceration of the epidermis, necrosis, rupture and discontinuity of collagen fibres in the dermis without any inflammatory response. Molecular identification matched the organism to Cladosporium spp, Curvularia spp, Exserohilum spp, Bipolaris spp (100%) and Alternaria spp (97%), all of which have been associated with phaeohyphomycosis. Phaeohyphomycosis should be included as a differential diagnosis of cutaneous lesions in chiropterans.